ANALISIS FAKTOR YANG BERPENGARUH TERHADAP IPM MENGGUNAKAN REGRESI LINEAR BERGANDA - Zakiyatul Fitriyah; Syafira Irsalina; Aditya Rizq Herlandy K; Edy Widodo (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
Development becomes a tool to achieve the goals of a nation. Meanwhile, economic growth is used as an indicator to determine the success of a country's development. HDI is a measuring tool to determine the level of development. Indonesia's HDI is included in the high category, including West Java and Banten provinces. There are allegations that the Covid-19 pandemic in 2020 affected the factors that formed the HDI. This study aims to determine the description of HDI and the influence of factors forming HDI consisting of AHH, RLS, HLS, and per capita expenditure. The secondary data used is sourced from the Central Statistics Agency (BPS) of the Republic of Indonesia. This research method is multiple regression analysis. Based on the study results, the partial test showed that the variables AHH, RLS, HLS, and per capita expenditure had a significant positive effect on the Regency/City HDI variable in the Provinces of West Java and Banten in 2020